Empirical analysis of buyer power - Walter Beckert (Centre for Microdata Methods and Practice (cemmap), 2009)
This paper provides a comprehensive econometric framework for the empirical analysis of buyer power. It encompasses the two main features of pricing schemes in business-to-business relationships: nonlinear price schedules and bargaining over rents. Disentangling them is critical to the empirical identification of buyer power. Testable predictions from the theoretical analysis are delineated, and a pragmatic empirical methodology is presented. It is readily implementable on the basis of transaction data, routinely collected by antitrust authorities. The empirical framework is illustrated using data from the UK brick industry. The paper emphasizes the importance of controlling for endogeneity of volumes and for heterogeneity across buyers and sellers.
Keywords: D43; L11; L12; L14; L42; C23; C78; 330; buyer power; bargaining; nonlinear prices; transaction panel data; Marktmacht; Nachfragemacht; Verhandlungstheorie; Ziegelindustrie; Großbritannien